Investigation of Resilience among Teachers and in Teacher Education - Bordás, Andrea (Central European Journal of Educational Research, 2023)
In recent decades, we have witnessed an increasingly widespread and complex use of the concept of resilience. The aim of the present study is to present a holistic concept of resilience that, thanks to its systems theory basis, can be applied very well in educational sciences, including research on teacher training, the institutional environment of teachers, their well-being at work, professional development, or even in the analysis of practical pedagogical situations. The dynamic interactive model of resilience (Shafi, & Templeton, 2020) allows for the examination of the resilience of learners, teachers and the institution, and even the examination of students, educators and teacher training institutions involved in teacher training. In the second part of the study, we present resilience development programs that have proven to be effective in teacher training and further training (BRiTE, ENTREE), which, with their complexity, are well suited to the dynamic interactive model of resilience discussed above.